Java programming 24-hour trainer - Fain, Yakov (Wrox guides, 2011)
A unique book-and-video package presented by Java guru Yakov Fain As one of the most popular software languages for building Web applications, Java is often the first programming language developers learn. The latest version includes numerous updates that both novice and experienced developers need to know. Covers the concepts, terms, and programming practices of Java to create Web applications